Grid balancing with a large‐scale electrolyser providing primary reserve. Issue 16 (29th November 2020) - Samani, Arash E.; D'Amicis, Anna; De Kooning, Jeroen D.M.; Bozalakov, Dimitar; Silva, Paolo; Vandevelde, Lieven
Abstract : As the share of renewable energy sources increases, the grid frequency becomes more unstable. Therefore, grid balancing services will become more important in the future. Dedicated devices can be installed close to the point where off‐shore wind farms are connected to the transmission grid on land. There, they can be used to attenuate power variations, reduce congestion and offer grid balancing. The provision of these ancillary services can create considerable additional economic revenue. In this study, the provision of the primary reserve by means of a large hydrogen electrolyser of 25 MW is investigated for the specific case of the Belgian transmission system. The revenue of the provision of the frequency containment reserve (FCR) is analysed on a techno‐economic model, including capital costs, operational costs, the revenue of the generated hydrogen and oxygen products and the ancillary service income. The revenue depends strongly on the contracted power band. Therefore, it is optimised to yield maximum revenue. The results show that providing FCR creates considerable additional revenue. Therefore, a large electrolyser can be a good candidate to buffer excess renewable energy into green gas while simultaneously providing the grid support.